Feminist evaluation: case study of graça machel trust women creating wealth programme - Mokoena, Refilwe (My University, 2022)
Feminist evaluation assesses the value or merit of a policy, programme or other initiative with a focus on the gender-based inequality and its contribution to social injustice. Evaluation results and processes are then used to act and advocate for gender equality. Applying a feminist lens to evaluation increases the likelihood that systemic gender-based norms, beliefs and discrimination will be examined and addressed. This, in turn, can increase the evaluation’s utility as feminist evaluation approaches involve users in defining and addressing these norms. This study applied feminist evaluation principles to the Graça Machel Trust Women Creating Wealth (WCW) programme in Malawi, South Africa, Tanzania and Zambia, to examine how these principles affect the usefulness of the evaluation. The research used Alkin’s (2017) concept of the two categories of the Program Evaluation Utility Standards – those to do with the evaluation and those to do with the evaluator – to define utility. The study evaluated the WCW by employing the Most Significant Change approach, complemented by document review. The study’s research component included semi-structured key informant interviews with feminist evaluation experts, the WCW programme manager and a literature review. Results revealed the ways in which the two feminist principles contributed to the evaluation-related utility standards, namely attention to stakeholders and meaningful processes and products. Adding a feminist lens to the evaluation context analysis of the WCW programme made visible the gender norms and beliefs in the external environment as well as those demonstrated by the programme. This context review also brought to light the power dynamics within the programme. This information strengthened attention to more marginalized stakeholders, which increased the study’s utility. The use of feminist principles outlined the ways of knowing espoused by the WCW programme and showed that some ways of knowing and learning were privileged over others, even in an all-women initiative The use of feminist evaluation principles and the Most Significant incited some learning and reflection on feminist programming on the part of WCW staff. The full investigation into the evaluation’s utility remained underdeveloped, however, due to logistical and time constraints. This presents an opportunity for further and future research into the effect of feminist evaluation on evaluation utility in Africa.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Public & Development Sector Monitoring and Evaluation to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Feminist evaluation; Women trust; Wealth programme; UCTD; SDG-5: Gender equality